(Black)Rock the vote: Index funds and opposition to management - Farizo, Joseph D. (Journal of Corporate Finance, 2022)
I show index funds are more likely to oppose management on contentious management sponsored proposals at firms held only by their family's index funds than on proposals at firms co-held by their family's active funds. Additionally, shareholder proposals garner a greater level of support by index funds when the firm's shares are not simultaneously held by a fund's same-family active funds. Consistent with “locked-in” motives to monitor, these results imply index funds participate as more engaged voters when same-family active funds avoid holding positions in a firm.